Light of my life [videorecording (DVD)] - Affleck, Casey, 1975-; Affleck, Casey, 1975-; Pniowsky, Anna; Bower, Tom, 1938-; Moss, Elisabeth, 1982- (Paramount Pictures Home Entertainment, 2019)
The world has been caught in an epidemic that killed all of the Earth's population. A father and his child begin to navigate this new landscape which is no longer hospitable or safe. Along the way, he must fight off dangers that threaten the family as well as a lack of moral compasses in others they meet. It's a journey of survival that leads to treacherous territories and the ultimate quest.